2018
DOI: 10.1186/s12911-018-0704-9
|View full text |Cite
|
Sign up to set email alerts
|

Designing mHealth for maternity services in primary health facilities in a low-income setting – lessons from a partially successful implementation

Abstract: BackgroundIncreasing mobile phone ownership, functionality and access to mobile-broad band internet services has triggered growing interest to harness the potential of mobile phone technology to improve health services in low-income settings. The present project aimed at designing an mHealth system that assists midlevel health workers to provide better maternal health care services by automating the data collection and decision-making process. This paper describes the development process and technical aspects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 24 publications
0
43
0
Order By: Relevance
“…-To propose new tools compatible with the ODK suite or with the ODK-X suite [20], [21], [22], [23], [24]; -To make improvements to a single component of the ODK suite or the ODK-X suite, without having to touch all the others [25], [26]; -To use one or some of the components of the ODK or ODK-X suite without having to use the whole suite. The tools of the two suites can even be used with other technologies that do not belong to ODK [31], [32], [34], [38], [40], [41]; -To extend a component of the ODK or ODK-X suite by adding new functionalities and then to use this extension with the other components of the suite [27], [28], [29].…”
Section: Table-iii: Studied Articles By Themementioning
confidence: 99%
See 1 more Smart Citation
“…-To propose new tools compatible with the ODK suite or with the ODK-X suite [20], [21], [22], [23], [24]; -To make improvements to a single component of the ODK suite or the ODK-X suite, without having to touch all the others [25], [26]; -To use one or some of the components of the ODK or ODK-X suite without having to use the whole suite. The tools of the two suites can even be used with other technologies that do not belong to ODK [31], [32], [34], [38], [40], [41]; -To extend a component of the ODK or ODK-X suite by adding new functionalities and then to use this extension with the other components of the suite [27], [28], [29].…”
Section: Table-iii: Studied Articles By Themementioning
confidence: 99%
“…3 [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [15], [40], [41], [42], [43] Use case of ODK. 15…”
Section: Referencesmentioning
confidence: 99%
“…MPAs are increasingly used in low-and middle-income countries for a wide range of applications, although applications in this setting are far exceeded by applications in high-income settings [12]. In sub-Saharan Africa and in the area of SRH, apps have been deployed to the public to support family planning [13] and to healthcare workers for improving provider quality of maternal and neonatal care [14][15][16][17][18][19][20]. To our knowledge, this is the rst report of an app deployed to members of the public to increase access to SRH information, goods, and services in the low-income setting.…”
Section: Discussionmentioning
confidence: 99%
“…According to this review, the most frequently reported barriers to the implementation of telemedicine services are cost 17,18,20,21,16,22,[23][24][25] and infrastructure. 13,17,18,21,22,24,26 The initial cost of establishing telemedicine services is very high, and to function telemedicine services in rural or remote areas for underserved communities needs telecommunication expenses, training (health personnel and 20 2013 Cross-sectional Cost, technical support, internet connection Mengesha et al 27 2013 Case study An internet connection and technical support system Abera et al 21 2014 Mixed method Cost, availability of technical support, Internet connection, ICT infrastructure, technological infrastructure, readiness, staff turnover Medhanyie et al 13 2015 Cross-sectional Health system, resistance to change, ICT infrastructure, awareness, language, poor application design, and technically challenged staff.…”
Section: Summary Of Main Findingsmentioning
confidence: 99%
“…According to this review, the most frequently reported barriers to the implementation of telemedicine services are cost 17,18,20,21,16,22,[23][24][25] and infrastructure. 13,17,18,21,22,24,26 The initial cost of establishing telemedicine services is very high, and to function telemedicine services in rural or remote areas for underserved communities needs telecommunication expenses, training (health personnel and 20 2013 Cross-sectional Cost, technical support, internet connection Mengesha et al 27 2013 Case study An internet connection and technical support system Abera et al 21 2014 Mixed method Cost, availability of technical support, Internet connection, ICT infrastructure, technological infrastructure, readiness, staff turnover Medhanyie et al 13 2015 Cross-sectional Health system, resistance to change, ICT infrastructure, awareness, language, poor application design, and technically challenged staff. Xue et al 16 2015 Cross-sectional The technical support system, resistance to change, anxiety, costs Dusabe-Richards et al 19 2016 Mixed-method Network coverage, technical support system, language, phone (mobile), socioeconomic status Barkman and Weinehall 22 2017 Descriptive case report Reimbursement, infrastructures, cost Biruk and Abetu 32 2018 Cross-sectional awareness Steege et al 23 2018 Costs, level of education, culture, phone (mobile), awareness Shiferaw et al 24 2018 Cross-sectional Cost, health system, culture, staff turnover, ICT infrastructure, electricity, phone (mobile), service integration, internet, awareness Harding et al 25 2019 Descriptive case report Electricity, e-health literacy, health system, telecommunication service, cost, internet connection, phone (mobile), human resources Dessie Gashu et al 26 2020 RCT ICT infrastructure, e-health literacy, phone (smart mobile)…”
Section: Summary Of Main Findingsmentioning
confidence: 99%